Evaluation of performance of acoustic materials - a case study in Brazilian civil construction - ZANNIN, P. H.T.; FERREIRA, J. A.C. (Archives of Acoustics, 2006)
Urban noises are emitted simultaneously by a wide variety of sources, such as, transportation and activities encountered in large cities. Many studies show that traffic noise followed by noise produced by neighbours are the main disturbing sources. Considering that both traffic and neighbour noise upset people inside their homes, it is possible to conclude that these homes do not display good performance of one of their purposes, which is the one of providing acoustic comfort. This fact is critical in Brazilian homes, as opposed to countries such as Germany and the USA, since these countries have specific rules for acoustic properties of materials used in civil construction, and Brazil does not. The goal of the present study is to show the acoustic performance of materials routinely used in Brazilian civil construction. Measurement procedures both in situ and in the laboratory are presented to determine acoustic performance of the materials, such as: insulation coefficient for air propagation. The results have shown that the acoustic performance of Brazilian constructions, are under international standard.